EFFECTIVENESS ADMINISTRATION OF SOME NATURAL SUBSTANCES ON THE COAGULATION OF RUBBER (Hevea brasiliensis): EFEKTIVITAS PEMBERIAN BEBERAPA BAHAN ALAMI TERHADAP KOAGULASI LATEKS KARET (Hevea brasiliensis) - Dewi Yana; Lukman Martunis; Mizar Liyanda; Ika Rezvani Aprita; Yusnidar (PT. ROCE WISDOM ACEH, 2024)
Coagulation is one of the processes of bringing together rubber grains contained in latex liquid so that a lump is formed. This study aims to determine the effectiveness of freezing rubber from natural materials such as star fruit, lime, and noni, palm sap. This research was carried out in Punkie Village, Kaway XVI Sub-district, Aceh Barat District from August 2023 until completion. The experimental design used is a non-factorial Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications, namely: K (control), MKD (noni), JNP (lime), NAN (palm sap), BMW (star fruit ). The study results show that the administration of some natural substances has a very significant effect on the coagulation of rubber; the most effective natural substance to coagulate rubber is noni.